2012
DOI: 10.1111/apt.12038
|View full text |Cite
|
Sign up to set email alerts
|

Non‐alcoholic fatty liver disease (NAFLD) is associated with low level of physical activity: a population‐based study

Abstract: SUMMARY BackgroundHigh intensity exercise improves metabolic status and may potentially mobilise hepatic fat.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
117
0
12

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 216 publications
(144 citation statements)
references
References 32 publications
7
117
0
12
Order By: Relevance
“…Other studies focused on the nutritional assessments of patients with NAFLD have further documented increased consump tion of low nutrient, high sodium and high fat foods, especially diets high in meat derived fats and lower amounts of fresh fruits 107,108 . In addition to these dietary habits, individ uals with fatty liver were found to have very low physical activity levels and increased sitting times compared with healthy individuals [109][110][111] . The prevalence of NAFLD is also related to socioeco nomic factors, but their exact role is debated.…”
Section: Risk Factors: Nature or Nurture?mentioning
confidence: 99%
“…Other studies focused on the nutritional assessments of patients with NAFLD have further documented increased consump tion of low nutrient, high sodium and high fat foods, especially diets high in meat derived fats and lower amounts of fresh fruits 107,108 . In addition to these dietary habits, individ uals with fatty liver were found to have very low physical activity levels and increased sitting times compared with healthy individuals [109][110][111] . The prevalence of NAFLD is also related to socioeco nomic factors, but their exact role is debated.…”
Section: Risk Factors: Nature or Nurture?mentioning
confidence: 99%
“…High fructose consumption may increase the risk of NASH and advanced fibrosis, although the association may be confounded by excess calorie intake or by unhealthy lifestyles and sedentary behaviour [10] , which are more common in NAFLD [11] .…”
Section: Pathogenesis: Lifestyle and Genesmentioning
confidence: 99%
“…Both cohort and population-based studies have demonstrated an independent relationship between low level of physical activity and poor fitness and the prevalence of NAFLD. 12,13 Clinical studies have shown that exercise interventions resulted in decreases in hepatic lipids 14,15 and fatty acid availability 14 in conjunction with an enhancement in insulin-stimulated glucose disposal. 16 Similarly, significant reductions in hepatic lipid contents and metabolic complications after exercise training were observed in Otsuka Long-Evans Tokushima Fatty (OLETF) rats 17 and obese Zucker rats 18 and mice.…”
Section: Introductionmentioning
confidence: 99%